Blood and animal rituals in Mesopotamia - Alrikabi, Nael Hammod (Al-Adab Journal, 2020)
The Mesopotamian civilization was distinguished by several features, among which were the existence of civilization and the beginning of religious cultures, which played an important role in the development of agricultural villages and populations and the emergence of major cities in them. Because of the environmental changes and the presence of natural forces that led him to worship it and avoided its anger resulting from torrential rains, floods, and strong winds, etc., which necessitated the population to offer sacrifices and offerings to the gods, and whenever the progress was many and large, then God would be satisfied with him, and from here the residents of Mesopotamia found that it is better The sacrifices are sacrificed for animal slaughter. Blood flow is evidence of the flow of life, as blood is the symbol of life and eternity. The rituals of Mesopotamia have gone through several stages, and with various events changed by the political, economic and environmental conditions, and many different rituals have arisen, in which the residents of Mesopotamia were able to express their religious, political and economic status, And researchers and specialists in archeology were able to study the religious side and the gods on the one hand, the political conditions, the system of government, the king, and the mandate of the covenant on the other side through the ages of Mesopotamia. And they tried the residents of Mesopotamia to use some rituals and insert them into myths and stories, which showed to the citizen in that era that the goal of sacrifices offered by him is part of his existence in this life, but that some rituals are very important in his death, so he or his family must provide sacrifices and sacrifices to the gods so that Settle for them.